Bypassing Energy Barriers in Fiber-Polymer Torrefaction - Xu, Zhuo; Kolapkar, Shreyas S.; Zinchik, Stas; Bar-Ziv, Ezra; Ewurum, Lucky; McDonald, Armando G.; Klinger, Jordan; Fillerup, Eric; Schaller, Kastli; Pilgrim, Corey (Frontiers in Energy Research, 2021)
The amount of waste generation has been increasing with a significant amount being landfilled. These non-recyclable wastes contain large number of fiber and plastic wastes which can be treated with thermal processes to turn them into energy sources since they have high calorific values, are abundant and usually tipping fees are paid to handle them. This paper studied the torrefaction of non-recyclable paper (fiber) wastes, mixed plastic wastes (MPW) and their blends at different ratios in the temperature range of 250oC-400oC through thermogravimetric analysis (TGA). The solid residues after the experiments were analyzed by nuclear magnetic resonance (NMR) spectroscopy. Significant synergy between fiber and MPW were observed at the range 250°C-300°C, showing both increase in the reaction rate as well as the overall mass loss. At 250°C, the maximum mass loss rate was more than two times higher and the mass loss at the end of the experiments were also much higher compared to the expected results. In addition, synergy was weakened with an increase of temperature, disappearing at 400 °C. The existence of such interactions between fiber and plastic wastes indicates that the natural energy barriers during the individual torrefaction in paper waste or plastic waste could be bypassed, and the torrefaction of fiber and plastic blend can be achieved at lower temperatures and/or shorter residence times. The MPW and fiber wastes were also compounded by extrusion (to produce pellets) at 220 °C with different blend ratios. The fiber-MPW pellets from extrusion were characterized by IR spectroscopy, rheology, thermal analysis and flexural properties and showed significant chemical changes from the non-extruded blends at the same ratios. From IR characterization, it was found that there was significant increase in hydroxyl (OH) group on account of the carbonyl (C=O) and etheric (C-O-C) groups. The interaction between paper and MPW can be attributed to the plastic polymers acting as a hydrogen donor during the reactive extrusion process. Synergistic effects were also found from mechanical and rheological properties.